ZULLISAYN TRADITION AND ISSUES OF CREATIVE INFLUENCE (Scientific journal of the Fergana State University, 2024)
The article talks about the characteristics of Zullisanaynism and the most used lyrical genres during the time when Zahiriddin Muhammad Babur lived.